Antibiotic Treatment Duration for Community-Acquired Pneumonia in Outpatient Children in High-Income Countries—A Systematic Review and Meta-Analysis. (17th May 2022) - Kuitunen, Ilari; Jääskeläinen, Johanna; Korppi, Matti; Renko, Marjo
Abstract: Background: The optimal treatment duration of community-acquired pneumonia (CAP) in children has been controversial in high-income countries. We conducted a meta-analysis to compare short antibiotic treatment (3–5 days) with longer treatment (7–10 days) among children aged ≥6 months. Methods: On 31 January 2022, we searched PubMed, Scopus, and Web of Science databases for studies published in English from 2003 to 2022. We included randomized controlled trials focusing on antibiotic treatment duration in children with CAP treated as outpatients. We calculated risk differences (RDs) with 95% confidence intervals and used the fixed-effect model (low heterogeneity). Our main outcome was treatment failure, defined as need for retreatment or hospitalization within 1 month. Our secondary outcome was presence of antibiotic-related harms. Results: A total of 541 studies were screened, and 4 studies with 1541 children were included in the review. Three studies had low risk of bias, and one had some concerns. All 4 studies assessed treatment failures, and the RD was 0.1% (95% confidence interval, −3.0% to 2.0%) with high quality of evidence. Two studies (1194 children) assessed adverse events related to antibiotic treatment, and the RD was 0.0% (−5.0% to 5.0%) with moderate quality of evidence. The diagnostic criteria varied between the included studies. Conclusions: A short antibiotic treatment duration of 3–5 days was equally effective and safe compared with the longer (current) recommendation of 7–10 days in children aged ≥6 months with CAP. We suggest that short antibiotic courses can be implemented in treatment of pediatric CAP. Abstract : Based on the meta-analysis of 4 randomized controlled studies with 1541 children, short antibiotic treatment (3–5 days) was as effective as the longer treatment (7–10 days) for community-acquired pneumonia in children in high-income countries.